Joinville and his book The Life of Saint Louis IX as a source for the Seventh Crusade against Egypt 647-648 AH / 1249-1250 AD: (A comparative study with Islamic sources) - Al-Yasari, Hayder (Al-Adab Journal, 2023)
The topic of the research revolves around the French historian Joinville and his book The Life of Saint Louis, in which he dealt with the events and facts of the Seventh Crusade against Egypt from the year 647 AH / 1249 AD to the year 648 AH / 1250 AD during the reign of the French King Louis IX and the study of this author as a Latin source on this campaign in comparison with Islamic historical sources. Through this study, we found that the historian Joinville was distinguished by his talent in accurately describing the events and details of the Seventh Crusade against Egypt, because he was one of the knights of this campaign and an eyewitness to its facts and circumstances, and by virtue of being very close to the French king, and he represents a model for the Frankish crusader knight nascent The European feudal society during the Middle Ages with its ideas, its feudal tendency, and its vision of Muslims and the Crusades, especially since it belonged to the French barons class, a class that had its weight and gravity in French society at the time. Therefore, it represents the Latin viewpoint, contrary to the view presented by Arab-Islamic sources on the facts and circumstances of this campaign against Egypt, and therefore his book "The Life of Saint Louis" is a great record of the history of King Louis IX, feudal France, and the Seventh Crusade against Egypt.